2010
DOI: 10.1017/s0043933910000243
|View full text |Cite
|
Sign up to set email alerts
|

Delay in feed access and spread of hatch: importance of early nutrition

Abstract: In a commercial hatchery, chicks (or poults) hatch over a 24-48 hour period. All chicks remain in the incubator until the majority of the chicks have emerged from the shell. Once removed from the incubator, the newly hatched chick has to undergo several hatchery treatments and is then transported before being placed on the broiler farm. This means that, under practical conditions, chicks are deprived of feed and water for up to 72 hours. In addition, the time of hatch within the hatching window and the spread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
127
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 49 publications
0
127
0
5
Order By: Relevance
“…As the spread of hatch increases and thus the HW, the time of first access to feed and water also increases. This delay in access to feed for day-old chicks ultimately impairs post hatch growth (Decuypere et al, 2001, Gonzales et al, 2003, Willemsen et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…As the spread of hatch increases and thus the HW, the time of first access to feed and water also increases. This delay in access to feed for day-old chicks ultimately impairs post hatch growth (Decuypere et al, 2001, Gonzales et al, 2003, Willemsen et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…and physiological (pancreatic and digestive enzymes) developments including increased surface area of nutrient digestion and absorption during the post-hatch period (Yadav et al, 2010). On the other hand, under practical conditions, a fasting period of 72 h after hatching during transportation to the broiler farm is generally common, due to variation in hatching time and logistics (Willemsen et al, 2010). In conclusion, the morphological development of digestive system and small intestine is impaired when chicks have delayed access to diet after hatching (Sklan and Noy, 2000;Van Den Brand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the chicks subsequently undergo processing and are then transported to the broiler farm. Thus, chicks can be deprived of feed and water for up to 72 h (Willemsen et al, 2010). It has been shown that feed and water deprivation after hatch leads to dehydration (van de Ven et al, 2009) and impairs welfare and post-hatch performance with respect to growth, immune system activation, digestive enzyme stimulation and organ development (Gonzales et al, 2003;Willemsen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chicks can be deprived of feed and water for up to 72 h (Willemsen et al, 2010). It has been shown that feed and water deprivation after hatch leads to dehydration (van de Ven et al, 2009) and impairs welfare and post-hatch performance with respect to growth, immune system activation, digestive enzyme stimulation and organ development (Gonzales et al, 2003;Willemsen et al, 2010). Therefore, the start of feed and water deprivation should be considered from the individual time of hatch and not from the end of incubation (Careghi et al, 2005) in order to reduce welfare issues and maintain health, as the day-old chick is the starting material to realise a high-quality broiler flock at slaughter age (Tona et al, 2003).…”
Section: Introductionmentioning
confidence: 99%